Cognitive poetic Analysis of Hidden Transcript in Two Selected Songs by Sam Kapisa and Arnold Ap - Awom, Iriano Yedija Petrus (Bahasa Indonesia Prima, 2025)
The Biaknese has a rich singing tradition. This tradition usually has a gnomic function, in the form of advice or wise words in dealing with various phenomena in their lives. In the social and political context, this tradition also equips the Biaknese in making criticism while avoiding retaliation due to their vulnerable position. This indirectness is a method often used by sub-ordinate or oppressed groups, which James Scott calls as hidden transcript. This research discusses hidden transcript messages in two songs by Sam Kapisa and Arnold Ap, “Manyei sima” and “Arbanya ifo amsam.” Both songs use metaphorical expression inspired by the ecological life of the Biaknese such as the sea, and its animals like birds and marine life. The purpose of this research is to analyze the implied meaning hidden in these metaphors. The method used in this research is qualitative and content analysis to analyze the hidden transcript in the text of the two songs. In particular, this study refers to the concepts of Peter Stockwell and George Lakoff, cognitive poetic and conceptual metaphors with two-domain (target-source) mapping model to infer explicit and implied meanings. The results of the discussion show that the second layer of meaning, although universal, is somehow very reflective because it is determined by the local content specific to the Biaknese and Papuans. Specifically, this finding justifies the existence of hidden transcript elements in the form of metaphor, anonymity, and euphemism in both songs.